DEA Window Analysis of Indonesian Banking Industry Efficiency During COVID-19 - Ririn Riani (SMART Insight, 2022)
crises and inefficiency, particularly in the banking sector. As a result, policymakers need information comparing the efficiency of different types of banks so they can develop appropriate regulations. The purpose of this research is to measure and compare the intertemporal efficiency of Islamic and conventional banks in Indonesia using Data Envelopment Analysis and DEA window analysis. This study examines the stability and efficiency of the Indonesian Banking industry from 2015 to 2020, along with the years 2019 and 2020, which highlight the Covid-19 pandemic era. The results revealed that Islamic banking received a score of 0.66, higher than conventional banking's score of 0.59. However, both exhibit a similar pattern in which the average level of efficiency decreases during the Covid-19 pandemic. From the perspective of efficiency stability analysis through various summary statistics such as standard deviation (SD), Long Distance per Window (LDW), Long Distance per Period (LDP), and Long Distance per Year (LDY), BRI, BRI Syariah, and BTN have the most relatively stable efficiency values among Indonesian banks. This study found that from 2015 to 2020, BRI is the most stable and efficient bank in Indonesia. This study suggests that Indonesia's conventional and Islamic banking systems must maximize their available resources and advance their technological capabilities to increase productivity in special circumstances like the current Covid-19 pandemic.